EVALUASI USABILITY SISTEM E-LEARNING SEBAGAI APLIKASI PENDUKUNG PROSES PEMBELAJARAN DI PERGURUAN TINGGI MENGGUNAKAN USE QUESTIONNAIRE - Sahfitri, Vivi; Ulfa, Maria (Universitas Bina Darma, 2015)
Implementation of elearning can help the learning process in college. Measurements using Usability emphasis on the effectiveness, efficiency and user satisfaction. This study aimed to evaluate the use of elearning as a support in the learning process in Higher Education. Instruments used in this measurement is to use a variable that contains the USE Questionnaire usefulness (U), Satisfaction (S) and Ease of use and Ease of Learning (E). Each of these variables will be elaborated into a package statement in the questionnaire using a Likert scale. Testing will be done using statistical calculations with application tools and application processing (SPPS) and excel application. The results provide empirical evidence about the influence of variables Usefulness, Ease of use and ease of learning the satisfaction variables either partially or simultaneously, also gave evidence about the dominant factors on the use of e-learning systems.